2005
DOI: 10.1128/aem.71.11.6501-6507.2005
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Partial Characterization of Antagonistic Peptides Produced by Paenibacillus sp. Strain B2 Isolated from the Sorghum Mycorrhizosphere

Abstract: Paenibacillus sp. strain B2, isolated from the mycorrhizosphere of sorghum colonized by Glomus mosseae, produces an antagonistic factor. This factor has a broad spectrum of activity against gram-positive and gram-negative bacteria and also against fungi. The antagonistic factor was isolated from the bacterial culture medium and purified by cation-exchange, reverse-phase, and size exclusion chromatography. The purified factor could be separated into three active compounds following characterization by amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 35 publications
0
64
0
2
Order By: Relevance
“…In the present study, we analyzed the possibility of eliciting plant defense responses by paenimyxin, an antagonistic compound isolated from the PGPR Paenibacillus sp. strain B2 (43). For this purpose, M. truncatula cell suspensions were used and a pathosystem between M. truncatula and F. acuminatum was established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we analyzed the possibility of eliciting plant defense responses by paenimyxin, an antagonistic compound isolated from the PGPR Paenibacillus sp. strain B2 (43). For this purpose, M. truncatula cell suspensions were used and a pathosystem between M. truncatula and F. acuminatum was established.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial growth conditions and purification of the Paenibacillus sp. strain B2 antagonistic factor (paenimyxin) were as described previously by Selim et al (43) and referred to as Superdex purified material.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of biocontrol formulation can be successful if microbial agents could survive during storage, as well as competitive and aggressiveness after inoculation process (Beatty and Jensen, 2002;Selim et al, 2005). In this study, although the potential suspension-based formulation showed good effect in blast suppression, but for large scale this formulation is less efficient in terms of packaging and use.…”
Section: Discussionmentioning
confidence: 85%
“…B2, isolated from the mycorrhizosphere of G. mosseae and identified by phylogenetic comparison of the 16S rRNA gene sequence and analytical profile index (API, analytical profile index) system, was antagonistic against various soilborne pathogens in vitro and reduced tomato root necrosis caused by P. nicotianae (Budi et al, 1999). This isolate displayed cellulolytic, proteolytic, chitinolytic and pectinolytic activities and was shown to liberate the antibiotic polymixin B1 and two other polymyxin-like compounds antagonistic among F. solani and F. acuminatum (Budi et al, 2000;Selim et al, 2005). Moreover, its presence resulted in disorganization of cell walls and/or cell contents of P. nicotianae and F. oxysporum observed by electron microscopy.…”
Section: Amb With Biocontrol Activitiesmentioning
confidence: 99%